Determination of cell fate along the anteroposterior axis of the Drosophila ventral midline. - Bossing, T.; Brand, A.H. (Development, 2006)
The Drosophila ventral midline has proven to be a useful model for understanding the function of central organizers during neurogenesis. The midline is similar to the vertebrate floor plate, in that it plays an essential role in cell fate determination in the lateral CNS and also, later, in axon pathfinding. Despite the importance of the midline, the specification of midline cell fates is still not well understood. Here, we show that most midline cells are determined not at the precursor cell stage, but as daughter cells. After the precursors divide, a combination of repression by Wingless and activation by Hedgehog induces expression of the proneural gene lethal of scute in the most anterior midline daughter cells of the neighbouring posterior segment. Hedgehog and Lethal of scute activate Engrailed in these anterior cells. Engrailed-positive midline cells develop into ventral unpaired median (VUM) neurons and the median neuroblast (MNB). Engrailed-negative midline cells develop into unpaired median interneurons (UMI), MP1 interneurons and midline glia.